Coronary artery embolism and culture-negative endocarditis post Bentall's procedure. Issue 10 (5th October 2021) - McNeill, Jared; Chew, Hong; Andresen, David; Muller, David; Granger, Emily; Wang, Louis W
Abstract: Infective endocarditis is an important cause of morbidity and mortality, which classically presents with fevers and nonspecific symptoms. Afebrile infective endocarditis with negative blood cultures makes diagnosis more challenging and delays in treatment can occur increasing the likelihood of complications. The presence of prosthetic heart valves places patients at an increased risk of infective endocarditis and the case described below highlights the importance of considering this diagnosis even if classic clinical features such as fever and raised inflammatory markers are not present, as well as discussing an unusual complication of infective endocarditis; coronary artery embolism leading to myocardial infarction.